The Monstrous Sea - Strang, Veronica (Lagoonscapes, 2023)
Through an anthropological lens, this essay examines the sea’s dual capacities to bring order and chaos. Drawing on a major comparative study, it examines hydro-theological water beings who personify the sea’s agentive powers, compose the world, and move spirit and matter through time and space. It explores the oceans’ capacities to consume human lives and threaten material stability, and considers how people respond to fears of being overwhelmed. It proposes that, rather than trying to control the sea with coastal fortifications, societies should seek more ecologically convivial solutions to stop climate change and support marine ecosystems.